2020
DOI: 10.3390/cancers12113306
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Sparing IMRT in Anal Cancer Patients Undergoing Concurrent Chemo-Radiation: Results of the First Phase of a Prospective Phase II Trial

Abstract: Purpose: to investigate the role of selective avoidance of hematopoietically active BM within the pelvis, as defined with 18FDG-PET, employing a targeted IMRT approach, to reduce acute hematologic toxicity (HT) profile in anal cancer patients undergoing concurrent chemo-radiation. Methods: a one-armed two-stage Simon’s design was selected to test the hypothesis that BM-sparing approach would improve by 20% the rate of G0–G2 (vs. G3–G4) HT, from 42% of RTOG 0529 historical data to 62% (α = 0.05 and the β = 0.20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
0
22
0
4
Order By: Relevance
“…Overall, our analysis showed grade 3–4 acute toxicity in 32.7% of patients, related mainly to local skin toxicity (25.6%). Grade 3–4 acute hematologic toxicity in our study was also limited (8.7%), despite the fact that selective approaches to spare the bone marrow were not routinely used in some institutions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our analysis showed grade 3–4 acute toxicity in 32.7% of patients, related mainly to local skin toxicity (25.6%). Grade 3–4 acute hematologic toxicity in our study was also limited (8.7%), despite the fact that selective approaches to spare the bone marrow were not routinely used in some institutions [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A validation of this new score system is mandatory to translate its use in clinical practice. More investigations are needed in this sense: if confirmed, these observations could add new elements to identify anal cancer patients likely to respond to CT-RT and those at high risk of persistence or relapse to tailor personalized treatment approaches and follow-up strategies [50].…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have also reported efforts to mitigate hematologic toxicity through selective avoidance of bone marrow with 18 FDG-PET guidance [ 120 , 121 ]. In a study of ten patients with locally advanced anal cancer, Franco et al outlined pelvic bone marrow defined as either the whole outer contour of pelvic bones or as active bone marrow identified using 18 FDG-PET.…”
Section: Hematologic and Genitourinary Toxicity: Implications Formentioning
confidence: 99%
“…The authors demonstrate a degree of reduction in dose to active pelvic bone marrow defined using 18 FDG-PET compared to optimization using iliac crests per RTOG 05-29, mirroring the reduction in dose when accounting for pelvic bone marrow outlined by the outer surface of external bony structures [ 120 ]. A single-arm prospective phase II study evaluated 18 FDG-PET and found that 18 FDG-PET-guided IMRT with bone marrow sparing was associated with a reduction in acute hematologic toxicity (19% experienced ≥G3 acute hematologic toxicity) [ 121 ]. These findings are exciting as they suggest further means through which hematologic toxicities may be reduced in patients with anal cancer; efforts are needed to identify patient populations most likely to benefit from the incorporation of 18 FDG-PET in IMRT planning [ 120 , 121 ].…”
Section: Hematologic and Genitourinary Toxicity: Implications Formentioning
confidence: 99%
See 1 more Smart Citation